2016
DOI: 10.1159/000445015
|View full text |Cite
|
Sign up to set email alerts
|

The Learning Curve in Robotic Pancreaticoduodenectomy

Abstract: Background/Purpose: Few data are available on the learning curve (LC) in robot-assisted pancreaticoduodenectomy (RAPD) and no study specifically addresses the LC of a single surgeon. Methods: The LC of a single surgeon in RAPD was determined using the cumulative sum method, based on operative time (OT). Data were extracted from a prospectively maintained database and analyzed retrospectively considering all events occurring within 90 days of index operation. Results: Seventy RAPD were analyzed. One operation w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
73
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 96 publications
(79 citation statements)
references
References 31 publications
5
73
1
Order By: Relevance
“…Previous studies have estimated that at least 50 cases for laparoscopic and 33 (up to 80 in one report) for robotic access are needed to achieve proficiency in performing them [24, 3739]. However, in all of them, operative time was taken into consideration to establish the completion of the learning curve.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have estimated that at least 50 cases for laparoscopic and 33 (up to 80 in one report) for robotic access are needed to achieve proficiency in performing them [24, 3739]. However, in all of them, operative time was taken into consideration to establish the completion of the learning curve.…”
Section: Discussionmentioning
confidence: 99%
“…The operative time in RPD could be shortened with increased experience and technical advances. Apart from the learning curve, many other factors may affect the surgeons' performance in RPD such as the absence of tactile feedback, magnified vision and instrument collisions when traversing broader operative fields [25][26][27]. In addition, aberrant or anomalous hepatic arterial anatomy may add to the difficulty of an Table 4 Operative time, lymph nodes harvested and estimated blood loss of RPD versus OPD and conversion of RPD The means and standard deviations were imputed from medians and ranges which were reported in each study Surg Endosc already technically challenging RPD [28].…”
Section: Discussionmentioning
confidence: 99%
“…This left an opening for robotic . Robotic pancreatoduodenectomy (RPD) offers improved three-dimensional imaging, 540° movement of surgical instruments, improved dexterity, and precision in complex tasks like vascular dissection and intracorporeal suturing (15)(16)(17).However, wide-spread adoption of RPD is hindered by a significant learning curve (18)(19)(20) and the low volume of surgeries relative to the trainees. Tseng et al analyzed the learning curve of high volume pancreatic surgeons for open PD and found that perioperative morbidity and Abstract: Minimally invasive surgery has revolutionized the face of surgical practice.…”
mentioning
confidence: 99%
“…However, wide-spread adoption of RPD is hindered by a significant learning curve (18)(19)(20) and the low volume of surgeries relative to the trainees. Tseng et al analyzed the learning curve of high volume pancreatic surgeons for open PD and found that perioperative morbidity and Abstract: Minimally invasive surgery has revolutionized the face of surgical practice.…”
mentioning
confidence: 99%